1984
DOI: 10.1002/jcu.1870120408
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time ultrasound of normal adrenal glands and small tumors

Abstract: The adrenals were studied prospectively with real-time ultrasound in a series of 60 healthy individuals and 13 patients with small adrenal masses sized 8-20 mm in diameter. In only one of the 60 healthy subjects was a normal adrenal gland delineated as a distinct hypoechoic structure. In all other instances only the highly echogenic suprarenal fat could be displayed. Visualization of small tumors was successful in 12 of 13 patients. The suprarenal area and small lesions were best demonstrated by a lateral inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
8
1
2
Order By: Relevance
“…Ultrasound, however, failed to detect the majority of diffuse adrenal hyperplasia in three series with mostly adult patients [1,27,28] except in one newborn with 21-OHase deficiency and two older patients with apparently long-standing untreated disease [6,7,27]. In contrast, the patients reported here show a distinct pattern of adrenal enlargement.…”
Section: Discussioncontrasting
confidence: 72%
“…Ultrasound, however, failed to detect the majority of diffuse adrenal hyperplasia in three series with mostly adult patients [1,27,28] except in one newborn with 21-OHase deficiency and two older patients with apparently long-standing untreated disease [6,7,27]. In contrast, the patients reported here show a distinct pattern of adrenal enlargement.…”
Section: Discussioncontrasting
confidence: 72%
“…However, Yeh (7) reported that adrenal masses as small as 6mm can be detected by US. A similar report by Giinther et al (4) described that US demonstrated 12 of 13 small adrenal masses 8 to 20mm in diameter. The delineation rate by initial CT examination in this series, especially for the left APA, was superior to US.…”
Section: Discussionmentioning
confidence: 53%
“…However, the usefulness of US to detect small adrenal tumors remains controversial (1)(2)(3)(4)(5). Recently, this problem has been offset with the improvement in resolution, thereby increasing the detection rate even for small adrenal tumors (3,4,6,7). Most aldosterone-producing adenomas (APA) are too small to be detected incidentally by imaging pro cedures (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal lesions · Unenhanced CT · Delayed enhanced CT · Chemical shift MRI · Adrenal scintigraphy · Adrenal biopsy Sonographie Die Sonographie vermag in Abhängig-keit von den Untersuchungsbedingungen und von der Erfahrung des Untersuchers Raumforderungen der Nebennieren ab einer Größe von 1 cm darzustellen [10]. Aufgrund der geringen Sensitivität (79%) und der noch geringeren Spezifität (61%) hat sich die Sonographie in der weiteren Abklä-rung von Nebennierenraumforderungen nicht durchgesetzt [10].…”
Section: Introductionunclassified
“…Aufgrund der geringen Sensitivität (79%) und der noch geringeren Spezifität (61%) hat sich die Sonographie in der weiteren Abklä-rung von Nebennierenraumforderungen nicht durchgesetzt [10].…”
Section: Introductionunclassified